التحري عن الانتقال الطبيعي لبعض الفيروسات ببذور اللوبياء. - اسماعيل, عماد دأود; درويش, يولا (Latakia University Journal -Biological Sciences Series, 2013)
أشارت نتائج اختيار البصمة النسيجية المناعية (TBIA) لـ 754 بذرة لوبياء جمعت من مناطق مختلفة من محافظة اللاذقية انتقال فيروسٍ واحدٍ فقط وهو فيروس موزاييك البازلياء المنقول بالبذور (PSbMV) من بين خمسة فيروسات استخدمت أمصالها في الاختيار (CMV, BYMV, PSbMV, BBMV and AMV). وتضمنت جميع المصادر بذوراً تحمل الفيروس وكانت نسبة الانتقال عالية حيث تراوحت ما بين 24,64% و37,50 %. تُعدّ هذه النتيجة التسجيل الأول محلياً لانتقال فيروس موزاييك البازلياء المنقول بالبذور إلى بذور اللوبياء. The results of Tissue-blot immunobinding assay (TBIA) of 754 samples of cowpea seeds collected from various regions in Lattakia province has showed the transmission of Pea seed borne mosaic virus (PSbMV) among five virus studied (CMV, BYMV, PSbMV, BBMV and AMV). Pea seed borne mosaic virus was detected on seeds collected from various locations in 24, 64% to 37, and 50%. This result is the first record of seed transmission of PSbMV in cowpea seeds.